Topik Modelling Skripsi Prodi Teknik Lingkungan di Jawa Timur Menggunakan Metode LDA - khoirinnisa', nurul; Khalid, Khalid; Wahyudi, Noor; Ardilla, Yunita (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
In higher education, the undergraduate thesis represents a tangible contribution of students to the development of scientific knowledge. In the field of Environmental Engineering, student research often focuses on issues that are closely related to both local and global environmental challenges. This study aims to analyze the main themes of undergraduate theses written by Environmental Engineering students in East Java using the Latent Dirichlet Allocation (LDA) method. The research data were collected from thesis titles and abstracts obtained from several universities. Through the application of LDA, several dominant themes were identified, including waste management, water quality, air pollution reduction, and the application of environmental treatment technologies. The results indicate that LDA is capable of uncovering research patterns and clustering topics that reflect the primary concerns of students in this field. These findings not only provide insights into the current research trends among students but also serve as a reference for curriculum development, research planning, and academic decision-making. Thus, this study contributes to improving the quality of education while mapping future research directions in Environmental Engineering.